Structural behaviour of cold-formed S700 high strength steel tubular members after exposure to fire - Zhong, Yukai (Nanyang Technological University, 2022)
High strength steel tubular members have been increasingly used in civil engineering due to their exceptional mechanical strengths. Significant improvement of high strength steel design guidance at ambient temperature has been achieved in recent years. However, the structural behaviour and design of high strength steel members after exposure to fire remains unexplored. The primary aim of the present thesis is therefore to experimentally and numerically investigate the structural behaviour of cold-formed high strength steel tubular members after exposure to fire, and develop relevant post-fire design guidance.